The Analysis Of Policy Implementation Of HIV/AIDS Management In Tanjung Morawa Puskesmas - Marbun, Romauli Anna; Karmayanti; Wahyuni, Siti; Sihombing, Yanna (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Human Immunodeficiency Virus infection and sexually transmitted infections are still a public health problem in the world and in Indonesia. People infected with HIV are still stigmatized, this happens because the level of education in the community is still mostly elementary school graduates. Barriers also occurred when conducting outreach to the community, because it was difficult to gather the community at the same time with reasons for work, school, or free time to be used for rest. This study aims to determine the implementation of HIV/AIDS prevention policies at the Tanjung Morawa Community Health Center. This research is important to do to find out the implementation of HIV/AIDS prevention policies at the Tanjung Morawa Community Health Center. The purpose of this study was to find out how the implementation of HIV/AIDS prevention policies at the Tanjung Morawa Community Health Center. This type of research is a qualitative research using in-depth interview data collection techniques, informants are selected purposively according to research needs, the data obtained in the research is then systematically processed at each stage to get the final results displayed in narrative form. The results showed that the transmission and authority in communication were good, the quantity and quality of resources were good, employee performance was optimal, fragmentation and SOP in the bureaucracy were good, but participation or the community was not optimal.